Flow through soil with initial gradient - BASAK, P. (MAUSAM, 1977)
A short review of the phenomenon of initial gradient in irrigation, drainage and consolidation problems is made and an analysis is presented to show that for the problem of horizontal and vertical capillary saturation, non recognition of initial gradient would lead to serious error in the estimation of ultimate travel length and the time rate on progress of saturation line.